A Deep Learning-Based Approach for High-Throughput Hypocotyl Phenotyping. Issue 4 (21st October 2019) - Dobos, Orsolya; Horvath, Peter; Nagy, Ferenc; Danka, Tivadar; Viczián, András
Abstract : A deep learning-based algorithm provides an adaptable tool for determining hypocotyl or coleoptile length of different plant species. Abstract: Hypocotyl length determination is a widely used method to phenotype young seedlings. The measurement itself has advanced from using rulers and millimeter papers to assessing digitized images but remains a labor-intensive, monotonous, and time-consuming procedure. To make high-throughput plant phenotyping possible, we developed a deep-learning–based approach to simplify and accelerate this method. Our pipeline does not require a specialized imaging system but works well with low-quality images produced with a simple flatbed scanner or a smartphone camera. Moreover, it is easily adaptable for a diverse range of datasets not restricted to Arabidopsis ( Arabidopsis thaliana ). Furthermore, we show that the accuracy of the method reaches human performance. We not only provide the full code at https://github.com/biomag-lab/hypocotyl-UNet, but also give detailed instructions on how the algorithm can be trained with custom data, tailoring it for the requirements and imaging setup of the user.